Nubbe natural products, source of molecular diversity for the design of new anticancer agents - Valli, Marilia [UNESP] (2014)
Natural products are an important source for the design of new drugs. This thesis aimed at the identification of bioactive natural products to be used as models for the design of compounds with antitumor properties. The lack of organized data is still one of the drawbacks in the natural products and medicinal chemistry area. Therefore, the compilation of accessible data of secondary metabolites from plant species or other sources is of great value, especially for the identification of molecular leads. This fact inspired us to propose as first objective of this thesis, the creation of the NuBBE database (NuBBEDB) containing botanical, chemical, and biological information of the secondary metabolites obtained and published by NuBBE in 15 years. This database can be useful not only for the current research in natural products of the group, but for the scientific society interested in bioactive compounds, metabolomics, and dereplication. A scientific paper describing the creation of the database was published in the Journal of Natural Products in 2013. NuBBEDB compounds were used as molecular source for the virtual screening with the protein tubulin. Based on the results of the virtual screening the biological evaluation of selected compounds was performed with the protein tubulin, and cell migration assays (Wound Healing and Boyden Chamber). The results of the biological assays indicated a series of guanidines and piplartine as active compounds. Piplartine was selected to be a model for the design of new compounds because it inhibited cell migration and is described in the literature as cytotoxic and selective, an interesting profile for this project. A series of 5 analogue compounds were designed and synthesized aiming at a better understanding of structure activity relationship and improvement of the biological activity. The compound designed by molecular simplification showed activity in the cell...